Assessing the impact of greenhouse gas emissions on corporate performance of oil and gas companies worldwide from 2019 to 2021 - De Guzman, Luis Raphael S. (Animo Repository, 2023)
Greenhouse gasses help the greenhouse effect by retaining heat in the Earth's atmosphere. Human activities, such as burning fossil fuels and industrial operations, have increased the amount of greenhouse gasses in the atmosphere, with the oil and gas sector being a major contributor. This study examined the greenhouse gas emissions of oil and gas companies worldwide and their impact on corporate performance. The researchers analyzed data from 2019 to 2021, using an independent variable: greenhouse gas emissions; dependent variables: return on assets, return on sales, and Tobin’s Q; and controlling variables: firm size, firm leverage, and capital intensity. The results were analyzed using descriptive statistics, assumptions test, partial f-tests, and simple regression analysis. The study’s findings show that GHG emissions for 2021 have negatively influenced corporate performance indicators, ROA and Tobin's Q only, with statistical significance of 5%. GHG emissions had a negative effect on ROA in the context of overall regression, with a negative coefficient and p value below the 5% level of significance. The researchers recommended management to practice sustainability to have competitive advantage, investors assess the ability of oil and gas companies to transition a low-carbon future, and regulatory bodies to incentivize oil and gas companies to reduce GHG emissions, and continuously review and update reporting standards for GHG emissions to reflect both evolving scientific understanding and international practices.